Chemical route derived bismuth ferrite thin films and nanomaterials. Issue 19 (6th April 2016) - Zhang, Qi; Sando, Daniel; Nagarajan, Valanoor
Abstract : In this review we focus on chemical route-derived bismuth ferrite (BiFeO3 – BFO) thin films and nanostructures. The review covers governing factors in a detailed and systematic manner so as to give readers a clear picture of the current state of the art in the development of nanostructured BFO via chemical routes. Abstract : Bismuth ferrite (BiFeO3 – BFO) is a prototypical lead-free single phase multiferroic which shows strong ferroelectric and antiferromagnetic properties simultaneously, together with high ferroelectric Curie temperature ( T FE ∼ 1103 K) and Néel temperature ( T N ∼ 643 K). BFO thin films and nanomaterials (collectively termed here 'nanostructured BFO') show many fascinating functional properties are not observed in the parent bulk compound. In this review we focus on chemical route-derived nanostructured BFO: thin films, nanowires and nanoparticles. The review covers governing factors in a detailed and systematic manner so as to give readers a clear picture of the current state of the art in the development of nanostructured BFO via chemical routes. We discuss the process pathways for each of the chemical (or soft) based synthesis techniques, highlighting both the advantages and challenges faced for each method. Specific emphasis is placed on understanding the role of each processing ingredient and development of optimized precursors. Finally we identify the opportunities posed by further development of chemical routes for this fascinating materials system. The review thus sheds significant insight into successfully achieving high-quality nanostructured BFO via chemical process techniques.